THE EFFECT OF DIGITAL SERVICE INNOVATION AND EMPLOYEE COMPETENCE ON PUBLIC SATISFACTION WITH SERVICE QUALITY AS A MEDIATOR - Adhitya Narrotama; Rudi Bambang Trisilo; Zainul Kisman (Jurnal Ilmiah Mahasiswa Ekonomi Syariah (JIMESHA), 2026)
Employing foreign workers can be done by any party in accordance with regulations, except for individual employers. However, the use of foreign workers must be carried out carefully and selectively, with attention to and prioritizing the use of domestic workers, including local workers, as long as they align with the required competencies. Every employer employing foreign workers is required to have written permission from the minister or designated official. This study aims to determine the effect of digital service innovation and employee competence on public satisfaction with service quality as a mediator at the Directorate General of Binapenta & PKK. This research is quantitative. The data analysis method used SEM-PLS analysis. The results of the hypothesis testing prove that digital service innovation, employee competence, and service quality have a significant effect on public satisfaction. Furthermore, digital service innovation and employee competency influence service quality. Furthermore, service quality mediates the influence of digital service innovation and employee competency on customer satisfaction.